Dampak Bullying Terhadap Kesehatan Mental Remaja: Tinjauan Psikologis dan Sosial: The Impact of Bullying on Adolescent Mental Health: A Psychological and Social Review - sirait, Judika Rubi Marta; Wisnusakti, Khrisna; Carmo, Elisa Adelia do (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Bullying, including verbal, physical, relational, and cyber forms, has become a major public health issue affecting adolescents worldwide. Exposure to bullying during adolescence is associated with various adverse psychological and social consequences, including depression, anxiety, chronic stress, sleep disturbances, trauma, suicidal ideation, and impaired interpersonal relationships. Despite the growing number of studies, comprehensive evidence synthesizing these impacts and their protective factors remains limited. This study aimed to systematically synthesize scientific evidence regarding the psychological and social impacts of bullying on adolescent mental health and to identify protective factors that may reduce these negative consequences. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature published between 2013 and 2025 was retrieved from Google Scholar, PubMed, ScienceDirect, DOAJ, and Garuda databases. Study quality was assessed using the Critical Appraisal Skills Programme (CASP) and Joanna Briggs Institute (JBI) checklists. Twenty-one eligible studies representing quantitative, qualitative, mixed-method, and systematic review designs were included and analyzed using thematic synthesis.   The findings consistently demonstrate that bullying substantially contributes to depression, anxiety, prolonged stress, sleep disorders, trauma, suicidal ideation, and social withdrawal among adolescents. Bullying also negatively affects interpersonal relationships and academic functioning, while family support, positive school climate, teacher involvement, and adaptive coping strategies emerge as important protective factors. These findings highlight the need for comprehensive multidisciplinary interventions involving families, schools, healthcare professionals, and communities to establish safe, inclusive, and supportive environments that promote adolescent mental well-being.